Effect of general anesthesia on postoperative pulmonary embolism - Junnan Xu; Xinyuan Yu; Yilong Shi; Fengyu Chen; Liang Wang; Jie Weng; Zhiyi Wang; Yingbin Deng (Annals of Medicine, 2025)
Background The influence of anesthesia type and duration on the occurrence of pulmonary embolism (PE) after surgery remains controversial. This study investigates the association between anesthesia type and duration with postoperative PE.Methods A retrospective cohort of adult patients undergoing surgery from May 2020 to August 2024 at large-scale general hospitals was analyzed. Multivariable logistic regression models were employed to adjust for potential confounders, and sensitivity analyses (using overlap weighting and array approach) were performed to validate the findings.Results A total of 178,052 patients were included in the analysis, of whom 91 developed PE after surgery. The median duration of general anesthesia (GA) was 1.72 h, with an interquartile range (IQR) of 1.17–2.52 h. The median duration of regional anesthesia was 1.54 h, with an IQR of 1.20–2.03 h. Anesthesia type and the duration of regional anesthesia were not associated with PE occurrence (adjusted odds ratio [aOR] [95% confidence interval, CI], 1.148 [0.671–2.098], p = 0.631), (aOR [95% CI], 1.117 [0.498–1.557], p = 0.738). The rates of PE consistently increased with GA prolongation (aOR [95% CI], 1.308 [1.176–1.432], p < 0.001). Compared with GA durations < 3 h, prolonged anesthesia was significantly associated with increased PE incidence (aOR [95% CI], 4.398 [2.585–7.565], p < 0.001). These findings were also confirmed by sensitivity analyses.Conclusions Our study demonstrates that prolonged GA, particularly > 3 h, significantly increases the risk of PE.